2022
DOI: 10.1038/s41598-022-10406-6
|View full text |Cite
|
Sign up to set email alerts
|

Comfort evaluation of ZnO coated fabrics by artificial neural network assisted with golden eagle optimizer model

Abstract: This paper introduces a novel technique to evaluate comfort properties of zinc oxide nanoparticles (ZnO NPs) coated woven fabrics. The proposed technique combines artificial neural network (ANN) and golden eagle optimizer (GEO) to ameliorate the training process of ANN. Neural networks are state-of-the-art machine learning models used for optimal state prediction of complex problems. Recent studies showed that the use of metaheuristic algorithms improve the prediction accuracy of ANN. GEO is the most advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 53 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…These include the count of hidden layers, the number of nodes within each hidden layer, the selection of the activation function for the hidden layer, the training function type, learning rate, and the number of training epochs 50 . In accordance with previous research findings, it has been demonstrated that the feedforward backpropagation ANN model attains optimal performance when configured with a singular hidden layer, a sigmoid tangent function for said hidden layer (Equation 9), and a pure linear activation function (Equation 10) [42][43][44][45][46]51 . This configuration was adopted in the present study.…”
Section: Modeling and Optimizationsupporting
confidence: 89%
“…These include the count of hidden layers, the number of nodes within each hidden layer, the selection of the activation function for the hidden layer, the training function type, learning rate, and the number of training epochs 50 . In accordance with previous research findings, it has been demonstrated that the feedforward backpropagation ANN model attains optimal performance when configured with a singular hidden layer, a sigmoid tangent function for said hidden layer (Equation 9), and a pure linear activation function (Equation 10) [42][43][44][45][46]51 . This configuration was adopted in the present study.…”
Section: Modeling and Optimizationsupporting
confidence: 89%
“…While MOGEO exhibits the capability to broaden the search range of the population through abrupt movements in the initial stages of iteration (Amor et al, 2022; Mohammadi‐Balani et al, 2021), continuously search for better solutions, and converges towards the global optimum during the iteration, practical evidence suggests that MOGEO still suffers from problems, such as inadequate population diversity and the susceptibility to local optima (Hu et al, 2022). To address these issues, an IMOGEO is proposed in this work.…”
Section: Trajectory Optimization Based On Multiobjective Golden Eagle...mentioning
confidence: 99%
“…While MOGEO exhibits the capability to broaden the search range of the population through abrupt movements in the initial stages of iteration (Amor et al, 2022;Mohammadi-Balani et al, 2021),…”
Section: Proposed Imogeomentioning
confidence: 99%
“…The GEO algorithm 33,34 is introduced by keeping the intelligent hunting behavior of the golden eagle, which adjusts its velocity of the spiral path on foraging. The golden eagle has a greater affinity for wandering around and monitoring its prey before it attacks the selected prey.…”
Section: Geomentioning
confidence: 99%